Marketing Analysis Of Education Services Muhammadiyah Elementary School Plus City of Salatiga - Sri Walji Hasthanti; Suyatmini .; Darsinah .; Marwanto . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2019)
This study is aimed to describe how the marketing educational service is applied in Muhammadiyah elementary school plus the city of Salatiga based on the marketing mix theory (product, price, place, promotion, people, physical evidence, and process). This qualitative research is conducted in Muhammadiyah elementary school plus the city of Salatiga. The data was collected by doing some interviews, observations, and documentation studies. This research is using a flow model of analysis. The results of this study show that (1) the school products are developed according to the potential benefits of academic, non-academic, and religious achievements, through promotion in various media by involving students, excellent service from all elements of the school. (2) The tuition fees are different for each grade level, not widely published and calculated globally for 1 school year. (3) The location of the school is supported by a comfortable environment for the teaching and learning process, away from the city crowd but easily accessible. (4) Promotion is carried out directly or indirectly by using various media, forging partnerships with government and private institutions as a form of service marketing breakthroughs, to win the title of an excellent school in Central Java. (5) Competent and outstanding human resources have the potential to improve school quality. (6) Physical evidence of the school is very representative, some places are strategic enough to be used as promotional media, as well as other physical facilities as a complement and support for learning. (7) the learning process is carried out with a fun and varied method and the use of social media as a means of information with the parents. The most prominent element in the marketing mix of educational services is the process.